Pendidikan Iman Bagi Kaum Muda Katolik Menurut Paus Fransiskus Dalam Seruan Apostolik Christus Vivit: Pendekatan, Tantangan, Dan Arah Pastoral - Tambunan, Hary Suhut; Mulyatno, Carolus Borromeus; Agustra, Markus Trio (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2025)
Nowadays, the negative impact of the Digital Era and globali-zation has brought many young people into a crisis situation regarding moral values. As a result, more and more young Catholics are not growing in their faith and commitment to love God and their fellow humans. The faith education of young Catholics, whether in the family, church, or formal schools, seems unable to overcome the negative impacts of the Digital Era and globalization. Pope Francis, in his Apostolic Exhortation, Christus Vivit, pays special attention to the faith education of young Catholics. So, in this writing, the author wants to identify and describe faith education for young Cath-olics based on Pope Francis' perspective. Previously, Marihot Simanjuntak and Monika Br Bangun (2023) had conducted research on the same theme, but the content was more about the application of theory and did not explain Pope Francis' views regarding faith education for young Catholics. This re-search was carried out using library research. The results of this research show that there are three main approaches to faith education, namely the love and understanding approach, the inclusive and contextual approach, and the community approach. So, faith education is not just a transfer of knowledge but must touch the heart and build a relationship with Christ. This article also discusses the challenges and rel-evant pastoral strategies.AbstrakDewasa ini, dampak negatif Era Digital dan globalisasi membawa masuk banyak orang muda dalam situasi krisis akan nilai-nilai moral. Akibatnya, semakin banyak orang muda Katolik yang tidak berkembang dalam iman dan komitmen untuk mencintai Allah dan sesama manusia. Pendidikan iman orang muda Katolik baik di lingkup keluarga, gereja, maupun sekolah formal seolah-olah tidak mampu mengatasi dampak negatif Era Digital dan globalisasi ini. Paus Fransiskus, dalam Seruan Apostoliknya, Christus Vivit, memberikan beberapa perhatian khusus bagi pendidikan iman kaum muda Katolik. Maka dalam penulisan ini, penulis hendak mengidentifikasi dan mendeskripsikan pendidikan iman bagi kaum muda Katolik berdasarkan perspektif Paus Fransiskus itu. Sebelumnya, Marihot Simanjuntak dan Monika Br Bangun (2023) sudah melakukan penelitian dengan tema yang sama, namun isinya lebih pada penerapan teori dan tidak menjelaskan pandangan Paus Fransiskus mengenai pendidikan iman bagi kaum muda Katolik. Penelitian ini dilakukan dengan studi Pustaka (library research). Hasil dari penelitian ini menunjukkan bahwa tiga pendekatan utama pendidikan iman, yaitu pendekatan kasih dan pengertian, pendekatan inklusif dan kontekstual dan pendekatan komunitas. Sehingga, pendidikan iman bukan hanya transfer pengetahuan, tetapi harus menyentuh hati dan membangun hubungan dengan Kristus. Artikel ini juga membahas tantangan, dan strategi pastoral yang relevan.